Formula 1 car wheel aerodynamics - Kellar, W. P.; Pearse, S. R. G.; Savill, A. M. (Sports Engineering, 1999)
A detailed project has been carried out to investigate the aerodynamic performance of a Formula 1 car front wheel. Experimental drag measurements were carried out on a 40% scale rig representing the front right-hand quarter of a generic Formula 1 car, with features such as the front wing and car body modelled accurately to generate a suitable flowfield around the wheel. Smoke flow visualization gave valuable insights into the major flow features and enabled understanding of how the wheel aerodynamic performance might be improved. Further visualization was carried out using a fully 3D CFD (Computational Fluid Dynamics) analysis of the test rig geometry, using state-of-the-art in-house geometry handling and CFD facilities based around an unstructured Navier-Stokes solver. Drag measurements were successfully obtained for a large range of typical car configurations, including front wing endplate variations. The experimental and computational flow visualization enabled a new front wing geometry to be designed, which gave a significant reduction in the drag of the wheel.